The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1152/ajpendo.00021.2015
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoline-like drugs improve insulin sensitivity through peripheral stimulation of adiponectin and AMPK pathways in a rat model of glucose intolerance

Abstract: Altered adiponectin signaling and chronic sympathetic hyperactivity have both been proposed as key factors in the pathogenesis of metabolic syndrome. We recently reported that activation of I1 imidazoline receptors (I1R) improves several symptoms of the metabolic syndrome through sympathoinhibition and increases adiponectin plasma levels in a rat model of metabolic syndrome (Fellmann L, Regnault V, Greney H, et al. J Pharmacol Exp Ther 346: 370-380, 2013). The present study was designed to explore the peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The results of this study showed that the pertussis toxin-sensitive G protein, phosphatidylinositol 3kinase/Akt GSK3b, is coupled with I 1 receptors (Yamanaka et al, 2010). Weiss et al (2015) showed that a ligand selective for I 1 receptors, LNP509, was able to increase the phosphorylation of 59 adenosine monophosphate-activated protein kinase (AMPK) in hepatic cells. AMPK is involved in cellular energy homeostasis.…”
Section: B Specific Binding Properties Selective Ligands Andmentioning
confidence: 82%
See 3 more Smart Citations
“…The results of this study showed that the pertussis toxin-sensitive G protein, phosphatidylinositol 3kinase/Akt GSK3b, is coupled with I 1 receptors (Yamanaka et al, 2010). Weiss et al (2015) showed that a ligand selective for I 1 receptors, LNP509, was able to increase the phosphorylation of 59 adenosine monophosphate-activated protein kinase (AMPK) in hepatic cells. AMPK is involved in cellular energy homeostasis.…”
Section: B Specific Binding Properties Selective Ligands Andmentioning
confidence: 82%
“…Nevertheless, using the binding technique, I 1 imidazoline receptors were shown to be present in the atria and ventricles of rat hearts (El-Ayoubi et al, 2002. Several teams have shown the existence of imidazoline binding sites in adipocytes of different species, including the hamster and rat (MacKinnon et al, 1989;Langin et al, 1990;Fellmann et al, 2013b;Weiss et al, 2015). Weiss et al (2015) demonstrated the existence of specific I 1 binding sites of imidazolines in hepatic cell lines, and Molderings et al (1995) also found fairly abundant amounts in the rat stomach.…”
Section: B Specific Binding Properties Selective Ligands Andmentioning
confidence: 99%
See 2 more Smart Citations
“…2), and the effect on adipocytokines, such as adiponectin as well. (Zuo et al 2015;Weiss et al 2015) 3) Direct effect on endothelial cells:…”
Section: ) Effect On the Metabolic Profilementioning
confidence: 99%